JAC Transitions - Mark Tucker; D. Dwayne Cartmell II (Journal of Applied Communications, 2008)
A 2009 issue of BOOKFORUM published a cartoon titled “The Lost Library — where all of the unwritten books go” (Shaw, 2009). As depicted in the cartoon, the Lost Library is a lonely place. Dusty shelves overflow with books and publications of untold value - novel and creative ideas that never see the light of day.
Keywords: JAC Transitions